AL-'ADAD WA AL-MA'DUD DALAM ALQURAN - Jabir, M. (State Institute of Islamic Studies (IAIN) Palu, 2006)
It is popularly known that Islamic sciences are written in Arabic books (yellow books). From those books, the Muslims learn a variety of Islamic sciences, including Nahw-Sharf (Arabic grammar and structure). Arabic is very important since traditional Islamic sciences such as Qur’an, hadith and earlier ulama’s thoughts are inherited in Arabic. One of the Qur’anic studies in the light of language is al-'Adad (count) wa al-Ma'dud (the things counted). This article tries to explore the two things based on grammatical sciences of Arabic found in the Qur’an. Kata Kunci: Al-‘Adad, al-Ma’dud, Bahasa Arab, Alquran